Phase II study of pegaspargase, etoposide, gemcitabine (PEG) followed by involved-field radiation therapy in early-stage extranodal natural killer/T-cell lymphoma - Demei Feng; Zhimin Yan; Bibo Fu; Shenrui Bai; Lewei Zhu; Robert Peter Gale; Zhongjun Xia; Yang Liang; Hua Wang (Hematology)
Objective: The prognosis of extra-nodal NK/T cell lymphoma (ENKTL) is poor, and the optimal therapy remains controversial. This study aims to evaluate the safety and efficacy of a new combined modality therapy.Methods: Phase-2 study of pegaspargase, etoposide and gemcitabine (PEG) combined with involved field radiation therapy (IFRT) in newly-diagnosed patients with early-stage ENKTL. Patients received 4 course of PEG followed by IFRT. The primary endpoints were complete response (CR), partial response (PR), and objective response rate (ORR) after IFRT. Secondary endpoints included progression-free survival (PFS), overall survival (OS) and adverse events.Results: 34 consecutive patients with Ann Arbor stage I/II were enrolled. 3 patients progressed on PEG, while the remaining 31 received IFRT. The ORR was 88.2% (30/34), included 28 (82.4%) complete and 2 (5.8%) partial responses. With a median follow-up of 56.0 months (Interquartile Range [IQR], 36.0-66.9 months), the estimated 5-year PFS and OS were 87.4% (95% Confidence Interval [CI],69.5%−94.8%) and 97.1% (95%CI, 80.1%−99.6%), respectively. Most adverse events were hematological and easily managed.Conclusions: PEG followed by IFRT is a safe and effective initial therapy for early-stage ENKTL, demonstrating impressive PFS and OS rates. This promising approach warrants further validation in a randomized controlled trial (Registered at Clinicaltrials.gov NCT02705508).Trial registration: ClinicalTrials.gov identifier: NCT02705508.